The individual in the religions of the ancient Mediterranean - Rüpke, Jörg (Oxford University Press, 2014)
Covering the Hellenistic and Imperial periods in both pagan polytheistic as well as Jewish monotheistic settings, this edited collection focuses on individuation in everyday religious practices across the ancient Mediterranean as identified in institutional developments and philosophical reflections on the self.